Soft-output equalization and TCM for wireless personal communication systems. - Yue Chen (IEEE Journal on selected areas in communications)
This paper investigates the use of a maximum a posteriori probability (MAP) algorithm to realize soft-output equalization in a concatenated equalization and trellis-coded modulation (TCM) decoding-based wireless communication system. Specifically, we first begin with a general MAP algorithm and then focus on studying Bahl's (1974) MAP and Lee's (1974) MAP algorithms. We then propose a modified version of Lee's MAP algorithm which is much simpler than the original, in terms of complexity, and is more practical. In particular, a very simple channel estimation method which employs orthogonal training sequences is proposed. In order to improve the system performance, equal-gain combining and selection diversity are also considered. Finally, we compare the performance of the MAP algorithm-based equalization with our previously proposed equalization scheme, which combines decision feedback equalization and TCM